Neurodiversity awareness: Is Malaysia there yet? - Aida A. Rahman; Woollard J. (International Journal of Evaluation and Research in Education (IJERE), 2019)
Scientific research on dyslexia has taken place for the past 50 years during which time arguments on brain deficiency have created tensions between education and cognitive neuroscience researchers. However, clinical research on dyslexia through functional magnetic resonance imaging (fMRI) has finally revealed that a dyslexic’s brain works differently. The findings have finally brought in a new synergy between research in education and cognitive neuroscience and empirically supported the neurodiversity movement. Recently, neurodiversity has been used as a framework for specific learning difficulties (SpLD) justice and to support dyslexia in inclusive education. This qualitative study was conducted to understand the Malaysian mainstream primary school teachers’ beliefs about SpLD and the current framework for Malaysian literacy support programme. The data collection is through social media focus group discussion and individual instant messaging interviews with forty-one teachers. The findings reveal that the current programme is built on theories of remediation and that the teachers have exhibited good levels of understanding of remediation, but not yet understand neurodiversity. It makes recommendations with regard to teacher professional development.